Orsakir langtímasykursteranotkunar á Íslandi og algengi forvarna gegn beinþynningu - Unnsteinn I. Júlíusson; Friðrik Vagn Guðjónsson; Björn Guðbjörnsson (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open Objective: The use of oral corticosteroids is one of the most common causes of iatrogenic osteoporosis. Recently, therapeutic guidelines dealing with the skeletal complication of corticosteroids have been published. Therefore, it is of interest to evaluate indication for long-term therapy with corticosteroids and the frequency of active intervention against steroid induced osteoporosis in daily clinical practise. Material and methods: After approval by the Committee on Medical Ethics and the Comission of Data Protection all recipes on corticosteroids in drugstores during two years period in the area of North-east Iceland (population 26,664) were gathered. Thereafter, information was collected from medical records at the Health Care Centres and the local Hospital. Patients who were taking corticosteroids for at least three months per year or in a repeated periods (totally three months annually) were included in the study. These patients also received a questionnaire concerning hormone relpacement therapy and dieatary consumption of calcium and D-vitamin. Results: One hundred and ninety-one patients were included in the study or 0.7% of the population. The mean age was 66 years (17-93) and 55% were females. Rheumatic and pulmonary disorders were the most frequent indication of the corticosteroid treatment. Twenty percents of the patients had expired an osteoporosis related fractures and 26% of the patients had supposed corticosteroids induced osteoporosis. Fifty-two percents of the patients were on sublimentary D-vitamin (fish liver oil) and 37% were taking calcium-tablets, while 91% of the patients were consuming milk products regularly. Nine percents of the patients were taking bisphosphonates and 21% of postmenopausal women were on hormone replacement therapy. Conclusions: Relatively few patients on long term corticosteroids are on primary prevention against corticosteroids induced osteoporosis, although several ...